FAKTOR-FAKTOR PENENTU HARGA LAHAN PERKOTAAN - Amin Novianto (Sustainable, Planning and Culture (SPACE) : Jurnal Perencanaan Wilayah dan Kota, 2022)
A city within the modern era grows rapidly as a result of urbanization and the expansion of various human activity The development of the city causes some puzzling situations, which the acquirable spaces in the city getting lesser, while on the other hand urbanization and human activity produce some force that cannot be delayed. This phenomenon creates greater competition for land use from the community. The competition itself causes another phenomenon of the urban land value, as the competition gets tighter, the urban land value also increases as time passes. Based on these occurrences, there are some key points to analyze the rise of land value; these key points can be viewed from the spatial and planning perspective. The key points can be concluded as the determinant of the land value. There are several ways to decide and analyze the determinant of land values, it depends on the methods and the perspective of how urban land values are viewed. This study will identify the numerous methods to figure the determinant of land values in the city with the study of some actual cases.